Schipropins A–J, structurally diverse triterpenoids from Schisandra propinqua. (February 2021) - Ma, Ren-Fen; Hu, Kun; Ding, Wen-Ping; Wang, Bin; He, Tao-Bin; Li, Xiao-Nian; Sun, Han-Dong; Puno, Pema-Tenzin
Abstract: Schipropins A–J, a series of undescribed lanostane and cycloartane-type triterpenoids, were isolated from the stems and leaves of Schisandra propinqua . Their structures, most of which were characterized by C-3/C-4 cleavage, were elucidated by extensive spectroscopic analyses. Noteworthily, the absolute configurations of schipropins A, D–G, and I were determined by single-crystal X-ray diffraction. Furthermore, schipropins E and G were found to possess moderate NO production inhibitory activity. Graphical abstract: Ten undescribed triterpenoids were isolated and characterized from the stems and leaves of Schisandra propinqua, and the structures of six compounds were validated by single-crystal X-ray diffraction. Image 1 Highlights: Ten undescribed triterpenoids were isolated and characterized from the stems and leaves of Schisandra propinqua . The chemical structures of six compounds were validated by single-crystal X-ray diffraction. Two compounds were found to possess moderate NO production inhibitory activity.